Association Between Mild Neurocognitive Disorder Due to Alzheimer's Disease and Possible Attention-deficit/Hyperactivity Disorder: A Case Report. Issue 3 (5th May 2022) - Carrillo, Pablo; Rey, Romain; Padovan, Catherine; Herrmann, Mathieu; Dorey, Jean-Michel
Abstract : Recent literature concerning attention-deficit/hyperactivity disorder (ADHD) underlines the persistence of this neurodevelopmental illness in older patients. Comorbidity with a neurodegenerative disease is thus possible. However, few studies have investigated this topic. To our knowledge, this is the first case report of such a possible association, which raises important questions about clinical presentation, symptoms, diagnosis, and treatment. A 72-year-old man, without any psychiatric history, presented with depression, subjective memory loss, and attention deficit and anxious symptoms, and was diagnosed with mild neurocognitive disorder due to Alzheimer's disease. However, the patient's attentional symptoms appeared to have been present since childhood. A formalized diagnostic interview assessing for ADHD did not allow for a clear diagnosis, possibly due to recall bias. The patient's anxiety symptoms also did not respond well to cognitive behavioral therapy coupled with different antidepressants. We hypothesized the presence of ADHD, with the symptoms balanced until now by the patient's high cognitive capacities, and we postulated that the onset of a neurogenerative process may have disrupted this balance. In this case report, we discuss symptom dimensionality, the interplay between neurodegenerative and neurodevelopmental diseases, and various treatment options. Attentional deficits and anxiety symptoms are frequent in mild neurocognitive disorders due to neurodegenerative illnesses. It is important to explore the time of onset of such symptoms since neurodegenerative processes can worsen neurodevelopmental conditions. Moreover, identification of a pre-existing neurodevelopmental condition can lead to alternative care and treatment options. In addition, the unexplained worsening of ADHD symptoms should prompt clinicians to assess for a neurodegenerative process.